Comprehensive Assessment of M-Proteins Using Nanobody Enrichment Coupled to MALDI-TOF Mass Spectrometry. (6th January 2020) - Mills, John R; Kohlhagen, Mindy C; Dasari, Surendra; Vanderboom, Patrick M; Kyle, Robert A; Katzmann, Jerry A; Willrich, Maria A V; Barnidge, David R; Dispenzieri, Angela; Murray, David L
Abstract: BACKGROUND: Electrophoretic separation of serum and urine proteins has played a central role in diagnosing and monitoring plasma cell disorders. Despite limitations in resolution and analytical sensitivity, plus the necessity for adjunct methods, protein gel electrophoresis and immunofixation electrophoresis (IFE) remain front-line tests. METHODS: We developed a MALDI mass spectrometry–based assay that was simple to perform, automatable, analytically sensitive, and applicable to analyzing the wide variety of monoclonal proteins (M-proteins) encountered clinically. This assay, called MASS-FIX, used the unique molecular mass signatures of the different Ig isotypes in combination with nanobody immunoenrichment to generate information-rich mass spectra from which M-proteins could be identified, isotyped, and quantified. The performance of MASS-FIX was compared to current gel-based electrophoresis assays. RESULTS: MASS-FIX detected all M-proteins that were detectable by urine or serum protein electrophoresis. In serial dilution studies, MASS-FIX was more analytically sensitive than IFE. For patient samples, MASS-FIX provided the same primary isotype information for 98% of serum M-proteins (n = 152) and 95% of urine M-proteins (n = 55). MASS-FIX accurately quantified M-protein to <1 g/dL, with reduced bias as compared to protein electrophoresis. Intraassay and interassay CVs were <20% across all samples having M-protein concentrations >0.045 g/dL, with the ability to detect M-proteins <0.01 g/dL. In addition, MASS-FIX could simultaneously measure κ:λ light chain ratios for IgG, IgA, and IgM. Retrospective serial monitoring of patients with myeloma posttreatment demonstrated that MASS-FIX provided equivalent quantitative information to either protein electrophoresis or the Hevylite ™ assay. CONCLUSIONS: MASS-FIX can advance how plasma cell disorders are screened, diagnosed, and monitored.